Textbooks History of Brazil for high school (1930-1945): among authors, teachings and curricula - Kênia Hilda MOREIRA (Ediciones Universidad de Salamanca, 2018)
This text aims to analyze the textbooks History of Brazil for high school in Vargas Era (1930-1945) with emphasis on the relationship between authors, teachings and curricula in the perspective of Brazilian education history. For both we selected three textbooks of two authors. We found some peculiarities about the textbooks in this period: the «new method» stands as didactic and pedagogical content, some approaches in the textbook precede to the curricula, and the presence of President Getúlio Vargas speeches reinforce the value of the «October Revolution of 1930» in these textbooks. This allows us to conclude, in line with Choppin (1992), the textbook as an educational instrument inscribed on a long tradition, is inseparable from teaching conditions of his time.